Repetitive transcranial magnetic stimulation in the management of poststroke depression - Amgad A.M Gabr; Mohamed Hamed; Mohammad Abdul-Fattah (Wolters Kluwer Medknow Publications, 2020)
Background Poststroke depression (PSD) occurs in nearly 33% of stroke survivors. Noteworthy, PSD might lead to severe consequences such as functional disability, poor rehabilitation outcomes, and quality of life, which in turn contribute noticeably to suicidal tendencies, restroke occurrence, and high mortality rate among survival patients. Aim This study was performed to show the psychiatric outcomes of repetitive transcranial magnetic stimulation (rTMS) in the management of PSD survivors. Patients and methods Patients with clinical and neuroradiological evidence consistent with either brainstem, hemispheric, or cerebellar ischemic stroke were included in this study. Hamilton depression rating scale and Beck depression inventory scores were performed for psychiatric assessment of these patients. Results In all, 40 patients were included in this study who developed PSD and fulfilled the eligibility criteria. There were 22 (55%) women and 18 (35%) men with a mean age of 64.1±9.3 years. All patients suffered from depression, 13 (32.5%) from severe depression, 27 (67.5%) have a complete response to rTMS not only at the end of the treatment protocol, but also after a month from the cessation of rTMS. There was a statistically significant difference regarding the levels of Hamilton depression rating scale 17 Beck depression inventory scores at baseline, end of treatment, and one month after the stoppage of treatment. Conclusions This study showed that rTMS is an effective, safe, and promising therapeutic treatment, mostly for severely depressed patients after stroke.